Analisis Faktor yang Memengaruhi Daya Minat Calon Mahasiswa Melanjutkan Studi ke Universitas Pendidikan Ganesha (Studi Kasus Tahun 2021) - I.K.I Krisna; G.S. Wijaya; A.A.N.Y. Panji; I.G.P.A. Arimbawa (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to describe the factors that influence and the factors that dominate the interest of prospective students to continue their studies at the Ganesha University of Education. The subjects of this research are prospective students who want to continue their studies at the Ganesha University of Education in 2021. The sample of this research subject was chosen randomly, with a total of 50 respondents. The data collection method used is the interview and questionnaire method and the research instrument used is the interview guide and questionnaire using a Likert scale. This research will provide various benefits, among others, as an enrichment of research related to the factors that influence the interest of students to continue their studies at a university, especially to the Ganesha Education University and can be used as a reference to find out the influencing factors and the most important factors. dominate a person's interest to continue their studies to college by certain agencies, especially Undiksha. The results of this study indicate that the factors that influence interest are factors of accreditation status, outcomes, environment, interests, motivation, costs, qualifications of educators, as well as self-efficacy factors and the most dominating factor is interest factor.